2002
DOI: 10.1074/jbc.m109986200
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Stimulation of the Surfactant Protein B Gene by STAT3 in Respiratory Epithelial Cells

Abstract: The function of the lung is dependent upon differentiation and proliferation of respiratory epithelial cells and the synthesis/secretion of surfactant lipids and proteins into air space. During the respiratory inflammatory response, cytokines produced by macrophages and epithelial cells in the respiratory system have significant influence on surfactant protein homeostasis. We report here that among family members of Janus family tyrosine kinase (JAK) and signal transducers and activators of transcription (STAT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
91
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(100 citation statements)
references
References 36 publications
8
91
0
1
Order By: Relevance
“…While its potential role in lung morphogenesis or function is presently unknown, in vitro studies demonstrated that STAT-3 regulated the expression of surfactant protein B (SP-B), binding and activating cis-active elements in the SftpB gene promoter (6). Its potential role in the regulation of surfactant homeostasis in respiratory epithelial cells in vivo has not been evaluated, however.…”
Section: For Review)mentioning
confidence: 99%
“…While its potential role in lung morphogenesis or function is presently unknown, in vitro studies demonstrated that STAT-3 regulated the expression of surfactant protein B (SP-B), binding and activating cis-active elements in the SftpB gene promoter (6). Its potential role in the regulation of surfactant homeostasis in respiratory epithelial cells in vivo has not been evaluated, however.…”
Section: For Review)mentioning
confidence: 99%
“…The centralized homeodomain is known to bind to other transcription factors, including retinoic acid receptors (RARs) (Yan et al, 2001), zinc finger GATA transcription-6 (GATA-6) (Liu et al, 2002;Weidenfeld et al, 2002), and nuclear factor of activated T cells (NFAT) (Dave et al, 2004). Finally, the COOH-terminus functionally interacts with the DNA repair protein thymine DNA glycosylase (TDG) (Missero et al, 2001), other transcriptional coactivators such as p300 (Bachurski et al, 2003;Grasberger et al, 2005), SRC-3, SRC-2, BR22 (amino acid 6-206) (Yang et al, 2001;2003), poly(adenosine diphosphate-ribose) polymerase-1 (PARP-1), PARP-2 (Maeda et al, 2006), and other transcription factors such as nuclear factor κB (NF-κB) (Islam and Mendelson, 2006), signal transducers and activators of transcription 3 (STAT3) (Yan et al, 2002), Drosophila mothers against decapentaplegic 3 (SMAD3) (Li et al, 2002), nuclear factor I (NFI) (Missero et al, 2001), and ezrinradixin-moesin (ERM) (Lin et al, 2006).…”
Section: Structure Of the Nkx2-1 Gene And Protein And Its Biologicalmentioning
confidence: 99%
“…The CCSP-rtTA transgenic mice were genotyped with an upstream primer corresponding to the CCSP promoter sequence (5Ј-ACTGCCCATTGCCCAAACAC-3Ј) and a downstream primer corresponding to the rtTA code region sequence (5Ј-AAAATCTTGC CAGCTTTCCCC-3Ј). CCSP-rtTA/(teto) 7 -CMV-Stat3C double-transgenic mice were generated from cross-breeding of the CCSP-rtTA transgenic mice and (teto) 7 -CMV-Stat3C transgenic mice.…”
Section: Generation Of Doxycycline-controlled Stat3c Transgenic Micementioning
confidence: 99%
“…In the absence of SP-B, neonatal lungs are collapsed during respiratory cycles that cause death after birth (10,11). Stat3 stimulates SP-B gene expression in respiratory epithelial cells in a synergistic manner with retinoid acid receptors (7,8). In an animal system, in which the Stat3 allele is selectively deleted in respiratory epithelial cells, surfactant proteins and lipids are decreased or absent in alveolar lavage material during hyperoxia.…”
mentioning
confidence: 99%
See 1 more Smart Citation